Teacher reflection – call for a transformative mindset. Issue 1 (2nd January 2023) - Tay, Lee Yong; Tan, Liang See; Aiyoob, Thaslim Begum; Tan, Jing Yi; Ong, Monica Woei Ling; Ratnam-Lim, Christina; Chua, Puay Huat
ABSTRACT: The main objective of this paper is to examine how teacher reflection could result in possible change in practice. The essential value of teacher reflection is to think about improvements to be made for practice. This paper adapted Ward and McCotter's reflection rubric into a Teacher Reflection survey scale to explore and examine the varying years of teaching experience, teaching level and designation on teachers' teaching practices. A total of 436 primary and secondary school mathematics teachers took part in an online survey. Confirmatory factor analyses were conducted to validate the survey instruments. Findings suggest that there were no major differences in teacher reflection based on their years of teaching experience, designation, and teaching levels. Correlational, regression, and path analyses of the three dimensions of teacher reflection (i.e. Focus, Inquiry, and Change ) and teacher Change Practise revealed interesting associations among these variables. Findings indicate that the Focus dimension is the basis of teacher reflection and from there it extends to the Inquiry and Change dimensions and ultimately to Change Practise . This study suggests that the focus on a transformative mindset based on intentional reflection is a powerful stimulus for change and growth in teaching practice.